2015
DOI: 10.1039/c5ay01499a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and selective extraction of multiple sulfonamides from aqueous samples based on Fe3O4–chitosan molecularly imprinted polymers

Abstract: A highly selective MIP-MDSPE/HPLC method for fast extraction and determination of seven SAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 49 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…Among them, sulfamethoxazole (SMX) is a sulfonamide bacteriostatic antibiotic that has been commonly used during the last 80 years to treat urinary tract infections due to its low cost and broad spectrum of activity to treat bacterial diseases [ 2 , 3 ]. However, the widespread and indiscriminate use of SMX, as of other antibiotics, constitutes a huge potential threat to human health and contaminates natural ecosystems by affecting aquatic and soil organisms [ 4 , 5 ]. Recently, SMX has been detected in effluents of sewage treatment plants (STP), and also in surface and groundwater [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, sulfamethoxazole (SMX) is a sulfonamide bacteriostatic antibiotic that has been commonly used during the last 80 years to treat urinary tract infections due to its low cost and broad spectrum of activity to treat bacterial diseases [ 2 , 3 ]. However, the widespread and indiscriminate use of SMX, as of other antibiotics, constitutes a huge potential threat to human health and contaminates natural ecosystems by affecting aquatic and soil organisms [ 4 , 5 ]. Recently, SMX has been detected in effluents of sewage treatment plants (STP), and also in surface and groundwater [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of SMX adsorption by MIPs, few works have been published, with most of them aiming at the analytic quantification of this antibiotic. For example, Qin et al [ 5 ] used Fe 3 -O 4 -chitosan MIPs for SMX selective extraction and determination in aqueous samples, with the produced materials having attained a maximum adsorption capacity of 4.32 mg g −1 . Zhao et al [ 25 ] prepared core–shell MIPs on the surface of magnetic carbon nanotubes (MCNTs@MIP) for SMX, the resulting material having a maximum SMX adsorption capacity from aqueous solution of 864.9 µg g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In most applications, magnetic chitosan sorbents were combined with other materials to prepare hybrid composites, such as GO [75,77,79e81,83,86,91] MIPs [60,63,69,70,78,80,81,88,92]; other polymers including polyaniline [59,66,68], polypyrrole [57,61,89], and polythiophene [62,64]; and even ILs [77], deep eutectic solvents [69,82], surfactants [71], and antibodies [84]. When dealing with magnetic GO/chitosan sorbents, the GO is added to the reaction solution during the crosslinking of chitosan in presence of the MNPs.…”
Section: Chitosan In Sorbent-based Microextraction Methodsmentioning
confidence: 99%
“…The vast majority of the developed methods have been used for the extraction of organic compounds, covering from drugs and antibiotics [38,39,45,46,57,60,61,70,80,87,92,94], pesticides [42,43,62,64,71,72], other persistent and emerging endocrine disruptor contaminants, to natural bioactive compounds [41,53,55,56,69,86,90], and pigments [47,51]. Among the endocrine disruptor contaminants, polycyclic aromatic hydrocarbons (PAHs) [78,97], polychlorinated and polybrominated biphenyls (PCBs and PBBs) [49,58,93], phthalate acid esters (PAEs) [52,66,89], parabens [40,54], phenols [59,99], and other food contaminants [80,88], can be cited.…”
Section: Analytical Applications With Chitosan-based Materials In Sorbent-based Microextractionmentioning
confidence: 99%
“…This highlights the challenge in working with real complex analytes. Qin et al 31 prepared chitosan‐based MMIP materials for the detection and removal of sulfonamides (a class of antibiotics) in water and sewage samples. It was found that 112 ng L −1 of sulfamethoxazole was in the sewage sample using MMIPs, whereas only 64 ng L −1 of sulfamethoxazole was found in the sample using a C‐18 extraction column.…”
Section: Magnetic Molecular Imprinted Polymer (Mmip)mentioning
confidence: 99%